Ignorance, Intention and Stochastic Outcomes - Katharina Momsen; Jana Friedrichsen; Stefano Piasenti (ZBW - Leibniz Information Centre for Economics, 2021)
In sequential interactions, both the first mover's intention and the outcome of his choice may influence the second mover's action. While outcomes are typically observable, intentions are more likely to be hidden, leaving potential wiggle room for the second mover when deciding on a reciprocating action. We employ a controlled experiment to investigate how intentions and outcome affect second mover actions and whether second movers use hidden information as an excuse to behave more selfishly. We find that second movers react both to the intention of the first mover and to the achieved outcome when they are fully informed about both, but the effect is stronger for intentions than outcomes. When intentions are not revealed by default, second movers select into information based on their inclination to behave more prosocially. While information avoidance is frequent and selfishness is higher with hidden information, we do not find evidence of a strategic exploitation of moral wiggle room.
Keywords: D91; C91; 330; information avoidance; dictator game; public good game; moral wiggleroom; intentions; reciprocity